Comprehensive Diagnostics of Diesel Locomotives with Hydraulic Transmission: Approaches and Methods - Bodnar, B. Y.; Ochkasov, O. B.; Bodnar, Y. B. (Science and Transport Progress, 2025)
Purpose. The main purpose of this article is to determine a generalized indicator of the energy efficiency of the diesel engine operating cycle, which takes into account the complex effect of thermodynamic, mechanical, and hydrodynamic losses that occur during its operation. The proposed indicator makes it possible to assess changes in diesel engine operation caused by a decrease in its thermal efficiency due to a deterioration in the combustion process of the fuel mixture, an increase in mechanical losses caused by the gradual wear of parts, as well as the appearance of additional malfunctions in its systems and components that affect the overall performance of the engine. Methodology. To achieve this goal, based on the results of experimental studies, we propose a method for determining the effective power of diesel engines of diesel locomotives TGM4 and TGM6–A with hydraulic transmission UGP750–1200PR, which is an integral indicator characterizing their technical condition and allowing to assess the quality of repair. Findings. Based on the experimental studies, a method for determining the effective power of diesel locomotives with a hydraulic transmission UGP750–1200PR during short-term loading by a starting torque converter in the turbine wheel «runaway” mode was developed. The method is based on measuring the diesel engine crankshaft speed and charge air pressure. The processing of experimental data allowed us to propose a method for estimating the effective power of a diesel engine as an integral indicator of its technical condition. This methodology makes it possible to determine the quality of repair of diesel locomotives TGM4 and TGM6–A with hydraulic transmission UGP750–1200PR, to detect hidden faults, to assess the general technical condition of the diesel engine without disassembly, and to determine the need for repair or adjustment of parameters. Originality. The work further developed methods for diagnosing power plants of diesel locomotives with hydraulic transmission and determining diagnostic parameters characterizing their technical condition. Practical value. The use of the proposed methodology for determining the effective power of diesel locomotives with hydraulic transmission UGP750–1200PR allows detecting hidden faults, assessing the general technical condition of the diesel engine without disassembling it, and determining the need for repair or adjustment of parameters.